Identidades, saberes e territorialidades no mundo do trabalho das pescadoras de camarão da ilha do tarará – Tefé (Am) - Santos, Rosa Maria Ferreira dos (2020)
Shrimp fishing carried out by women from Tarará Island in the municipality of Tefé-AM is the objective of this research, we seek to analyze the debate on the work of Amazonian women in the contemporary world, understanding their way of life and highlighting the territorialities and techniques developed in this activity, in addition to checking the ways of using and marketing the shrimp. We opted for the qualitative method of research in the nature of participant observation, as well as a methodological tool associated with the semistructured interview and bibliographic review of the main categories covered in the analysis, such as mode of production, work, women, fishing, territory and territoriality. All the work of making the equipment is carried out by the fishermen and is essential in this activity. The choice of fishing territories by women fishermen is defined according to the purpose of fishing, being carried out in different ways, forms and techniques. Among them, paneiro fishing, rapixé fishing, stingray fishing and finally tipuca fishing were described. In each of these modalities, we observe the capacity for social organization of work in fishing activities, as well as the construction, production and reproduction of territorialities expressed in the particularity of their ways of community life.